Increase in activin A may counteract decline in synaptic plasticity with age - Zheng, Fang; Dahlmanns, Marc; Kessler, Philipp; Alzheimer, Christian (Frontiers in Aging Neuroscience, 2024)
Activin A, a member of the transforming growth factor β (TGF-β) family, is widely recognized for its neurotrophic and neuroprotective function in the developing and injured brain, respectively. Moreover, in the healthy adult brain, activin A has been shown to tune signal processing at excitatory synapses in a fashion that improves cognitive performance. Because its level in human cerebrospinal fluid rises with age, we wondered whether activin A has a role in mitigating the gradual cognitive decline that healthy individuals experience in late-life. To interrogate the role of activin A in synaptic plasticity in the aging brain, we used an established transgenic mouse line, in which expression of a dominant-negative mutant of activin receptor IB (dnActRIB) serves to disrupt activin receptor signaling in a forebrain-specific fashion. In brain slices of young adult dnActRIB mice (2–4 months old), the NMDA receptor-dependent and -independent forms of long-term potentiation (LTP) at the Schaffer collateral—CA1 pyramidal cell synapse of the hippocampus were equally impaired relative to the extent of LTP measured in the wild-type preparation. Unexpectedly, the difference between the genotypes disappeared when the two forms of LTP were re-examined in slices from middle-aged mice (13–16 months old). Since the level of activin A and endogenous ActRIB both displayed a significant elevation in middle-aged hippocampus, we reasoned that with such a rise, the dominant-negative effect of the mutant receptors could be overcome. Substantiating this idea, we found that administration of recombinant activin A was indeed capable of restoring full-blown LTP in slices from young dnActRIB mice. Our data suggest that, beginning in the middle-aged brain, endogenous activin receptor signaling appears to become strengthened in an attempt to stave off cognitive decline. If further corroborated, this concept would also hold promise for new therapeutic venues to preserve cognitive functions in the aged brain.